2019
DOI: 10.1155/2019/1376980
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Asian-Pacific Oscillation on Precipitation in Central Eastern China during Autumn (1960–2016)

Abstract: e Asian-Pacific Oscillation (APO) plays an important role in precipitation in Central Eastern China (CEC). is study analyzed observational and reanalysis data to investigate CEC precipitation during autumn and its association with the APO. e APO index (APOI) was redefined, and an autumn CEC precipitation index (CECPI) was calculated to elucidate the relationship between the APO and CEC precipitation. Significant positive correlation (correlation coefficient: 0.60) was found between the APOI and CECPI. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…During summer, when the mid-upper troposphere is warmer over Asia, the troposphere above the North Pacific will be colder, and vice versa. The APO can exert substantial impacts on regional-global climatic change via the monsoon circulations and precipitation (Zhao et al, 2007(Zhao et al, , 2012aZhou et al, 2009;Liu et al, 2011;Zou et al, 2015;Hua et al, 2019;Lin et al, 2019Lin et al, , 2021, tropical cyclone activity (Zhou et al, 2008;Zou and Zhao, 2010), and variations in SST (Zhao et al, 2010(Zhao et al, , 2011(Zhao et al, , 2012b. Furthermore, the APO occurs throughout the year, not just in the summertime Lin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During summer, when the mid-upper troposphere is warmer over Asia, the troposphere above the North Pacific will be colder, and vice versa. The APO can exert substantial impacts on regional-global climatic change via the monsoon circulations and precipitation (Zhao et al, 2007(Zhao et al, , 2012aZhou et al, 2009;Liu et al, 2011;Zou et al, 2015;Hua et al, 2019;Lin et al, 2019Lin et al, , 2021, tropical cyclone activity (Zhou et al, 2008;Zou and Zhao, 2010), and variations in SST (Zhao et al, 2010(Zhao et al, , 2011(Zhao et al, , 2012b. Furthermore, the APO occurs throughout the year, not just in the summertime Lin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The APO can exert substantial impacts on regional-global climatic change via the monsoon circulations and precipitation (Zhao et al, 2007(Zhao et al, , 2012aZhou et al, 2009;Liu et al, 2011;Zou et al, 2015;Hua et al, 2019;Lin et al, 2019Lin et al, , 2021, tropical cyclone activity (Zhou et al, 2008;Zou and Zhao, 2010), and variations in SST (Zhao et al, 2010(Zhao et al, , 2011(Zhao et al, , 2012b. Furthermore, the APO occurs throughout the year, not just in the summertime Lin et al, 2019). In light of the findings of previous related studies, it has been suggested that the APO could be regarded as a crucial contributor to engendering climate change on regional-global scales.…”
Section: Introductionmentioning
confidence: 99%